Analisis Kemampuan Komunikasi Matematis Siswa SMP Berdasarkan Growth Mathematical Mindset - Siva Alyademi; Risma Hany Apriani; Sharikha Azka; Abigail Siregar; Fatihara Aliya Syahira; Nur Izzati (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
Mathematical communication skills are essential competencies that students need to develop in mathematics learning and may be influenced by (pola pikir matematis bertumbuh). This study aims to analyze junior high school students’ mathematical communication skills in terms of (pola pikir matematis bertumbuh). This research employed a descriptive qualitative approach involving three eighth-grade students representing the categories of strong (pola pikir matematis bertumbuh), tendency toward (pola pikir matematis bertumbuh), and tendency toward (pola pikir matematis tetap). Data were collected through questionnaires, mathematical communication skills tests, and interviews. The results showed that all three participants were able to express mathematical ideas and evaluate mathematical statements effectively. However, differences were found in the accuracy of mathematical terminology usage, conceptual understanding, and visual representation. The participant with a strong (pola pikir matematis bertumbuh) demonstrated better performance in reasoning, argumentation, and the use of mathematical models, while the other participants still experienced conceptual misconceptions and inaccuracies in visual representations. The findings indicate that (pola pikir matematis bertumbuh) plays a role in supporting the quality of students’ mathematical communication skills..